Session 1, Panel 1, Gummo, Karen. Storytelling, Peace and Conflict Resolution - Karen Gummo - Jarvis, Dale (2010)
Karen Gummo speaking at the 18th Annual Conference of Storytellers of Canada-Conteurs du Canada.